IMF Staff papers : Volume 6 No. 1. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1957)
The purpose of this paper is to bring monetary events, monetary data, and monetary problems within the framework of income analysis. The study tries to bridge gaps between: the views widely held on the relation between financial policies and payments questions; and the analytical tools used to explain payments developments. The failure to accommodate monetary factors in the analysis probably becomes most evident when questions are raised concerning the effects of specified monetary changes on income or on the balance of payments. The tools used in the economic analysis of situations are necessarily simplifications of a more general economic theory-simplifications which bring into focus the factors that seem most important in the classes of situation studied. The decision to treat domestic credit expansion as an autonomous variable is dictated by the purposes of the analysis. As statistically measured, credit expansion is a net concept, the difference between credit outstanding at the end and at the beginning of a period. Part of the repayments that occur during a period may be caused by new loans granted during this or a preceding period.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet